Estudo experimental do desempenho térmico de estruturas capilares de pó de cobre sinterizado em tubos de calor - Krambeck, Larissa (2018)
Heat pipes are heat transfer passive devices known as heat superconductors, due to the use of the latent heat of vaporization of a working fluid in a closed two-phase loop. The heat pipe is essentially composed of three components: an involucre, a working fluid, and a capillary structure. The wick is responsible for capillary pumping of the working fluid inside the heat pipe. In the present work was carried out an experimental evaluation of the thermal performance of copper sintered capillary structures in heat pipes. Due to their geometrical characteristics, the heat pipes can be used in the cooling of processors of electronic equipment, including spatial application. A model based on the operational limits (capillary, trailing, viscous, sonic, and boiling limits) was proposed for the sintered heat pipes and implemented in Engineering Equation SolverTM (EESTM) software. The heat pipes were fabricated from copper tubes with an outside diameter of 9.45 mm, an inner diameter of 7.75 mm and a total length of 200 mm. Three capillary structures of sintered copper powder with different thicknesses (Type #1, Type #2 and Type #3) were manufactured by the sintering process. The working fluid used was distilled water and each heat pipe was tested for several filling ratios. The condenser was cooled by forced convection of air and the evaporator was heated by a tape electric resistor and isolated from the external environment by an aeronautical thermal insulation. The heat pipes were tested experimentally for operating inclinations equal to 0°, + 45°, + 90°, – 45° e – 90°, under thermal loads between 5 W and 45 W. The metallic powder was characterized by Scanning Electron Microscopy (SEM), X-rayFluorescence Spectrometry (ED-XRF), and Laser Diffraction Granulometry. The sintered capillary structure was characterized in relation to porosity, permeability, critical radius, and thermal conductivity. The experimental results of the thermal performance of the sintered heat pipes showed that the copper powder and the sintering procedure used were suitable for application in copper heat pipes, since the heat pipes worked satisfactorily. The heat pipe Type #3 with a filling ratio of 100% of the evaporator volume presented the best performance, that is, the lower thermal resistance and lower operating temperature. In addition, sintered heat pipes have proven to be more efficient under adverse working conditions compared to other heat transfer passive devices (solid bar, thermosyphon, heat pipe with a screen wire and heat pipe with grooves).